Synergistic effect of octadecyl ammonium oxide and oleate amide propyl betaine and development of a foam drainage reagent for natural gas production - Gao, Minlan; Jia, Yijing; Lv, Shiyi; Dong, Sanbao; Wang, Manxue; Zhu, Shidong; Zhang, Jie; Chen, Gang (Comptes Rendus. Chimie, 2021)
Betaine surfactants are used widely in oil field chemistry as well as other industrial applications, but their foaming ability is very poor so that it cannot be used in foaming. In this work, the effect of octadecyl ammonium oxide on the foam properties of oleate amide propyl betaine, a new compound foaming reagent, is studied based on foam performance. Then, a foam drainage reagent of 0.5 wt% oleate amide propyl betaine and 0.1 wt% octadecyl ammonium oxide is developed for natural gas production. Its salt resistance, methanol resistance, high temperature resistance, anti-condensate oil performance, and emulsification ability are systematically evaluated. Furthermore, the factors affecting foam performance are analyzed. The results show that the compound foaming reagent has good anti-salt, anti-methanol, and anti-condensate oil properties for meeting application requirements. The microstructures of foams derived from different reagents reveal the stability mechanism. All results reflect the fact that compounding can expand their application range in different environments to various extents, which benefits the design and use of compound surfactants.